Challenges encountered by critical care unit managers in the large intensive care units - Mokgadi C. Matlakala; Martie C. Bezuidenhout; Annali D.H. Botha (Curationis, 2014)
Background: Nurses in intensive care units (ICUs) are exposed regularly to huge demands interms of fulfilling the many roles that are placed upon them. Unit managers, in particular, are responsible for the efficient management of the units and have the responsibilities of planning, organising, leading and controlling the daily activities in order to facilitate the achievement of the unit objectives.